A systematic review of ozone therapy for treating chronically refractory wounds and ulcers. Issue 4 (6th October 2021) - Wen, Qing; Liu, Dongying; Wang, Xian; Zhang, Yanli; Fang, Song; Qiu, Xianliang; Chen, Qiu
Abstract: This study aims at evaluating the efficacy and safety of ozone therapy for chronic wounds. The Cochrane Library, PubMed, Ovid Embase, Web of Science, and Chinese Biomedical Literature Database were searched. Randomised controlled trials (RCTs) about participants with chronic wounds were included. Risk of bias assessment was performed by the Cochrane risk‐of‐bias tool. A randomised‐effects model was applied to pool results according to the types of wounds or ulcers. Among 12 included studies, ozone was implemented by topical application (ozone gas bath, ozonated oil, ozone water flushing) and systematic applications including autologous blood immunomodulation and rectal insufflation. The results indicated compared with standard control therapy for diabetic foot ulcers, ozone therapy regardless of monotherapy or combined control treatment markedly accelerated the improvement of the wound area(standardised mean difference(SMD) = 66.54%, 95% confidence interval (CI) = [46.18, 86.90], P  < .00001) and reduced the amputation rate (risk ration (RR) = 0.36, 95% CI = [0.24, 0.54], P  < .00001). But there is no improvement in the proportion of participants with completely healed wounds and length of hospital stay. No adverse events associated with ozone treatment have been reported. And the efficacy of ozone therapy for other wound types is still uncertain because of no sufficient studies. More high‐quality randomised controlled trials are needed to confirm the efficacy and safety of ozone therapy for chronic wounds or ulcers.